Contraceptive methods continuation and its determinants among acceptors on repeat visits to a Nigerian University Teaching Hospital: a 10-year review - Abah, Matthias G.; Ocheche, Uduak S.; Abah, Iniobong; Etuk, Mbereobong S.; Markson, Emediong J. (International Journal Of Community Medicine And Public Health, 2024)
Background: Family planning is a known reproductive health modality for reducing the high maternal mortality in Nigeria. Contraceptive use and continuation is thus necessary to achieve its benefits. The study aimed to determine the contraceptive options and the factors associated with the continuation of contraceptive choices among women on repeat visits. Methods: This was a 10-year retrospective study of the family planning clinic register of all clients who presented for a repeat visit for contraceptive method continuation at the University of Uyo Teaching Hospital. Results: There were 6939 contraceptive acceptors on repeat visits aged between 14 and 50 years (mean 31.6 years, SD 5.4). The majority were 26 to 30 years (32.9%), had secondary education (54.6%), were multiparous (90.9%) and chose the subdermal implant (34.9%) and the intrauterine contraceptive devices (27.7%) for continuation. There was a significant association between the women`s age (Df=3, F=10.81, p<0.0001), their educational status (Df=6, Χ2=38.5583, p<0.0001), their parity (Df= 15, Χ2 =76.8644, p<0.0001) and the contraceptive method continued. Conclusions: An interest in long-acting reversible contraceptives for continuation was found, and this is significantly associated with their sociodemographic and obstetric characteristics; however, we recommend cross-sectional and focus-group inquiries among clients in the different contraceptive-specific categories for further information on the reasons for their choices at subsequent visits.